2010
DOI: 10.1016/j.ajhg.2010.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression and Genetic Variation in Response to Endoplasmic Reticulum Stress in Human Cells

Abstract: The accumulation of unfolded or misfolded proteins in the endoplasmic reticulum (ER) results in the condition called "ER stress," which induces the unfolded protein response (UPR), a complex cellular process that includes changes in expression of many genes. Failure to restore homeostasis in the ER is associated with human diseases. To identify the underlying changes in gene expression in response to ER stress, we induced ER stress in human B cells and then measured gene expression at ten time points. We follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
68
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 43 publications
9
68
0
2
Order By: Relevance
“…A comparison of the transcriptional response of whole flies to that of immortalized cell lines might nominate candidates for important conserved genes that show variation across species. To determine the overlap in variable ER stress genes in Drosophila and human, we compared our results with those reported by Dombroski et al for human cells (15). Of the conserved genes from our microarray study, 29% and 27% (early and late response, respectively) also showed expression variation in ER-stressed human cells (Dataset S2), as did, strikingly, 17% of the candidate ER stress genes from our association study (Dataset S5).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…A comparison of the transcriptional response of whole flies to that of immortalized cell lines might nominate candidates for important conserved genes that show variation across species. To determine the overlap in variable ER stress genes in Drosophila and human, we compared our results with those reported by Dombroski et al for human cells (15). Of the conserved genes from our microarray study, 29% and 27% (early and late response, respectively) also showed expression variation in ER-stressed human cells (Dataset S2), as did, strikingly, 17% of the candidate ER stress genes from our association study (Dataset S5).…”
Section: Discussionmentioning
confidence: 90%
“…Only one other published study investigated variation in ER stress response in any organism (15). That study measured the variation in ER stress transcriptional response in a collection of human cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations